Optimizing the Location of Pupuk PLO Branch Offices in the South Sumatra and South Sumatra Region - Haliawan, Prillia; Maulida, Sofia; Dwita, Febrisi (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
In the past five years, PLO fertilizers in the Southern Sumatra (Sumbagsel) operational area, which covers six provinces, have experienced 11 complaints originating from customer complaints (PBSN, retail market, and government), related partners such as trucking companies, warehouse parties, as well as internal PLO Fertilizer parties. These complaints have not been optimally managed because there is no PLO fertilizer branch office in the Sumbagsel working area. This has impacted the last five-year period, during which there has been a decline in PLO fertilizer sales in the Sumbagsel work area, with a decrease ranging from 10% to 15%. The aim of this research is to encourage the availability of PLO fertilizer branch offices in the Sumbagsel work area. The method in this study uses a qualitative approach with source triangulation through in-depth and structured interviews conducted repeatedly with informants who meet specific criteria. The research results identified six key success factors in determining strategic locations for PLO fertilizer branch offices in the Sumbagsel working area. These six factors were obtained from processing and analysis using the rating factor method. The processing results show that South Sumatra Province, with its capital Palembang, received the highest ranking weight compared to other provinces, which is 77.77. It is recommended that the city of Palembang be designated as the location for a branch office that manages and serves PLO Fertilizers in the South Sumatra working area. With six key success factors inherent in the city of Palembang, it is expected that operational productivity in the South Sumatra working area will grow and improve.